Social problem analysis of gender inequality in Donggala district - Ritha Safithri; Vitayanti Fattah; Moh Nutfa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The difference in treatment between women and men affects the lives of women and men themselves, either directly or indirectly in society, is a source of gender problems. Discussing gender issues is not a problem for women facing men, but gender issues are a common community problem, which requires a process of mutual awareness in the division of roles and positions that does not ignore the rights and obligations of women and men in the family, community and other lives. This study aims to produce an analysis of gender problems in people's lives in various fields of development. The method used is to conduct a qualitative analysis of the gender profile data contained in regional apparatus organizations in Donggala Regency. The results of the study indicate that gender issues are an important issue in the implementation of development in Donggala Regency, Central Sulawesi Province, this can be seen from the gender profile data so that an analysis of this is needed. The results of this analysis are expected to be the basis for the preparation of development programs in the fields of health, economy and employment, as well as in the fields of politics and decision-making. It is concluded that the high maternal mortality rate, the large number of poor female family heads and the low political participation of women are the main problems that are difficult to resolve.